PENGARUH KINERJA KEUANGAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (Pada Perusahaan Yang Terdaftar Di LQ45 Pada Bursa Efek Indonesia Periode 2010-2020) - Difa Restu Prabowo; Hidayat Wiweko (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Investors in Indonesian Capital Market increased by 56% throughout 2020. Things that must be considered in increasing investors is improving the quality of investors, so investors understand the investment instruments collected both from a fundamental and technical perspective. This study aims to analyze the effect of financial performance and dividend policy on firm value in companies listed on LQ45 on the Indonesia Stock Exchange for the 2010-2020 period. 12 companies listed in LQ45 were selected as samples using purposive sampling over a period of 11 years so the number of observations was 132 data. The data analysis method used is multiple linear regression analysis. The results showed that profitability and liquidity have a positive and significant effect on firm value. Meanwhile, leverage and dividend policy have no effect on firm value. Simultaneously variables of profitability, liquidity, leverage and dividend policy have a significant effect on the firm value.